2012
DOI: 10.1039/c2cc31884a
|View full text |Cite
|
Sign up to set email alerts
|

A facile and ecofriendly functionalization of multiwalled carbon nanotubes by an old mesoionic compound

Abstract: This work reports for the first time a straightforward solvent-free chemical procedure to gain access to Δ-1-pyrroline grafted onto multiwalled carbon nanotubes by the 1,3-dipolar cycloaddition of the mesoionic 4-methyl-2-phenyloxazol-5(4H)-one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 23 publications
(11 reference statements)
2
38
0
Order By: Relevance
“…3. In Raman spectra of pristine and EB-irradiated MWCNTs, the G-band at *1582 cm -1 is referred to the graphite vibration mode associated with the ordered sp 2 -hybridized carbon network; the D-band at *1348 cm -1 stems from local structural imperfections of the pristine MWCNT; and the 2D-band at *2691 cm -1 is assigned to the second order of the D-band [18,19]. When the relative intensity ratio of the D-and G-bands (I D /I G ) was evaluated as a measure of defects of the pristine and EB-irradiated MWCNTs, it was revealed that the I D /I G value of *1.07 for the pristine MWCNT increased to *1.17 for EB-irradiated MWCNT.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…3. In Raman spectra of pristine and EB-irradiated MWCNTs, the G-band at *1582 cm -1 is referred to the graphite vibration mode associated with the ordered sp 2 -hybridized carbon network; the D-band at *1348 cm -1 stems from local structural imperfections of the pristine MWCNT; and the 2D-band at *2691 cm -1 is assigned to the second order of the D-band [18,19]. When the relative intensity ratio of the D-and G-bands (I D /I G ) was evaluated as a measure of defects of the pristine and EB-irradiated MWCNTs, it was revealed that the I D /I G value of *1.07 for the pristine MWCNT increased to *1.17 for EB-irradiated MWCNT.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Other studies also observed a decline in I D /I G ratio with subsequent functionalization and this was attributed to the gradual removal of carbon debris which was generated during MWCNT oxidation. Likewise, it is an indication that epoxidation, epoxide ring opening and etherification steps did not cause further alteration in the sp 2 bonded carbon networks of the MWCNTs but might have reduced the diffuse Raman active defect sites at the sidewall of the nanotubes [42,44,45]. Thus, the modification steps performed on the MWCNT-COOH proved to be effective for attaching CE while maintaining the structure of the support.…”
Section: Structural Integrity Of the Materialsmentioning
confidence: 84%
“…Raman resonance of unmodified MWCNTs shows two prominent peaks at 1327 and 1580 nm À1 for D-and G-band, respectively. The defect mode D-band represents double resonance for amorphous carbon or it can be associated with local defects from structural imperfections of the MWCNTs [41,42]. The graphite mode G-band is related to the tangential in-plane vibration of sp 2 bonded carbons in MWCNTs [36,43].…”
Section: Structural Integrity Of the Materialsmentioning
confidence: 99%
“…The functionalized carbon nanomaterials have been characterized by XPS, microscopy (FEG-SEM, TEM, AFM), TGA and FT-IR to gain insights on structure, morphology and chemical composition. XPS spectra of pristine MWCNT showed only an intense C 1s peak [34] at a binding energy ca. 284 eV, while for the all functionalized CNT, the detection of a N 1s peak at ca.…”
Section: Synthesis and Characterization Of ˇ-Cd-mwcntmentioning
confidence: 98%